An overlooked alien species present on the coasts of Greece (Eastern Mediterranean): the polychaete Polycirrus twisti Potts (Polychaeta: Terebellidae) - SIMBOURA, N. (Mediterranean Marine Science, 2011)
The Terebellidae polychaete Polycirrus twisti Potts, 1928 had been confused in several previous records the Eastern Mediterranean with the co-generic species Polycirrus plumosusWollebaeck, 1912, because of incomplete specimens or unclear descriptions; therefore its presence in Greek seas had been overlooked. Specimens of Polycirrus twisti were currently identified from the Korinthiakos Gulf (Greece, Eastern Mediterranean), while older records from the Hellenic marine area, erroneously assigned toPolycirrus plumosus and recorded since 1983 (Rhodos island, Dodekanesse) were emended. Polycirrus twisti is an alien species, most likely introduced to the Mediterranean from the Suez Canal, while it was recently reported from the Southern coasts of Turkey (Levantine Sea). Its identification and report in Greek Seas increases the number of alien polychaete species in this area to 37 and offers a further evidence and link of its introduction and dispersion dynamics from the Suez Canal to the Levantine and Aegean Sea. The presence of the previously reported species Polycirrus plumosus in the Mediterranean Sea is therefore strongly questionable.